Interleukin-1 in the Response of Follicular Helper and Follicular Regulatory T Cells - Ritvo, Paul-Gydéon; Klatzmann, David (Frontiers in Immunology, 2019)
The role of interleukin-1 in the regulation of humoral responses is poorly documented, in contrast to its role in inflammation. Recent findings suggest there is an interleukin-1 axis in the follicular T cell control of B cell responses, involving interleukin-1 receptors (IL-1R1 and IL-1R2) and receptor antagonists (IL-1Ra). Here, we revisit the literature on this topic and conclude that targeting the interleukin-1 pathway should be a valuable therapeutic approach in many diseases involving excessive production of (auto)antibodies, such as autoimmune diseases or allergy.